Tourism Development Based On Sharia Models On Tourist Destinations In Padang City - Yanuar, Agus Zainul Arifin, Yulasmi (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to make a description of attractions to tourist destinations in North Sumatra. Sharia area is in the object of observation in West Sumatra province. The research subject is a tourist destination in the city. Sharia description analysis method (comparing between reality and expectations) the potential of sharia tourism is carried out through, a tourism manager survey of tourists on visits to tourism sites, and local government. This research was conducted by spreading, questionnaire, interview, and observation. The method of analyzing of data-fired different methods than Levene’s test for equality of SPSS variances and software. The result of the research proved that all tourists’ variables attraction, amanitas, accessibility and ancillary shows of the values were lower than the hope Levene’s Test for equality of variances proved which are considerable.